Pengaruh Pengungkapan Akuntansi Karbon Kinerja Lingkungan Terhadap Profitabilitas Perusahaan Sektor Farmasi Yang Terdaftar di BEI Tahun 2022 - Chandra Fitriyani Crisna Mukti; Ida Bagus Ketut Bayangkara (CV. Ulil Albab Corp, 2024)
The aim of this research is to find out the effect of accounting disclosures on the profitability of pharmaceutical sector companies in 2022. A quantitative approach is the method in this research. This type of research data is secondary data taken from annual reports and company sustainability reports via the idx.com data site and the company's official website. The population is 30 pharmaceutical sector companies listed on the IDX. The sample was used in 5 companies that met the required data criteria. The research collection technique used was SPSS 24. The results obtained from this research were that simultaneously disclosing carbon accounting and environmental performance had an effect on the profitability of pharmaceutical sector companies in 2022.